The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/eurheartj/ehab423
|View full text |Cite
|
Sign up to set email alerts
|

Early invasive coronary angiography and acute ischaemic heart failure outcomes

Abstract: Aims  While myocardial ischaemia plays a major role in the pathogenesis of heart failure (HF), the indications for coronary angiography during acute HF are not established. We determined the association of early coronary angiography during acute HF hospitalization with 2-year mortality, cardiovascular death, HF readmissions, and coronary revascularization. Methods and results  In a two-stage sampling process, we identified ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…15 Observational data from Ontario suggest that early invasive coronary angiography within 2 weeks of HF diagnosis is associated with four times higher rates of revascularization within 90 days, 26% lower morality and 16% lower heart failure readmissions at two years. 9 However, that study included those with known CAD and those presenting with acute coronary syndromes who are much more likely to benefit from immediate invasive angiography. Not surprisingly, we also found that early coronary assessment was associated with higher GDMT prescriptions (even prior to coronary assessment) and higher likelihood of revascularization.…”
Section: Coronary Assessment and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Observational data from Ontario suggest that early invasive coronary angiography within 2 weeks of HF diagnosis is associated with four times higher rates of revascularization within 90 days, 26% lower morality and 16% lower heart failure readmissions at two years. 9 However, that study included those with known CAD and those presenting with acute coronary syndromes who are much more likely to benefit from immediate invasive angiography. Not surprisingly, we also found that early coronary assessment was associated with higher GDMT prescriptions (even prior to coronary assessment) and higher likelihood of revascularization.…”
Section: Coronary Assessment and Outcomesmentioning
confidence: 99%
“…Observational studies suggest that coronary assessment during HF hospitalization or within 2 weeks of diagnosis is associated with higher use of medical therapy and revascularization, and with reduced mortality and rehospitalization. 8,9 Despite the evidence, most commercially-insured patients with HF do not undergo coronary assessment within 90 days, with disparities by county, patient demographics, and co-management by a cardiologist. 10 Women and persons of Black race are less likely to be referred for coronary assessment in other settings.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term prognosis for primary PCI and external CABG is similar, but the average length of hospital stay for PCI is shorter. In addition, a large number of modern clinics do not always have the opportunity to accept a patient urgently for surgery [9]. Therefore, it is necessary to develop simple clear criteria for selecting patients with acute myocardial infarction for emergency surgical revascularization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, heart failure is a challenge because of the multiplicity of potentially important outcomes including heart failure hospitalization, ischemia-related hospitalization, emergency department visits, sudden death, cardiovascular death, and worsening heart failure. 10 , 11 These outcomes may have different degrees of importance to subspecialist physicians (eg, heart failure specialists, cardiac electrophysiologists, interventional cardiologists, cardiac surgeons), generalists, and hospitalists. Based on our prior work engaging patients, 12 , 13 the outcomes that are important to patients extend beyond all-cause mortality.…”
mentioning
confidence: 99%